Strategi guru Pendidikan Agama Kristen Dalam Mempersiapkan Peserta Didik Menghadapi Ujian Semester - Ventje Andri Politon (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2022)
This paper aims to outline the strategies of Christian Religious Education teachers in the preparation of student semester exams. The approach used in this paper is with a literature study. The results of the discussion of this paper reveal that the strategy of Christian Education teachers in the preparation of semester exams in students, namely Christian Education teachers have a good work ethic, understand the nature of semester exam preparation well, and provide the right stages of exam preparation for students. The work ethic of Christian Education teachers and a good understanding of the nature of semester exam preparation are very important to note. The lack of work ethic and the lack of understanding of Christian Education teachers about the preparation of student examinations will affect the readiness of students in facing semester exams. Likewise with the stages of the preparation of the semester exam. Teachers of Christian Religious Education need to understand each stage of preparation for the exam. Work ethic, understanding, and implementation of good semester exam preparation is a strategy of Christian Education teachers in improving student learning outcomes. Tulisan ini bertujuan untuk menguraikan strategi guru Pendidikan Agama Kristen dalam persiapan ujian semester siswa. Pendekatan yang digunakan dalam tulisan ini ialah dengan kajian pustaka. Hasil pembahasan dari tulisan ini mengungkapkan bahwa strategi guru Pendidikan Agama Kristen dalam persiapan ujian semester pada siswa yaitu guru Pendidikan Agama Kristen memiliki etos kerja yang baik, memahami hakikat persiapan ujian semester dengan baik, serta memberikan tahapan-tahapan persiapan ujian yang tepat pada siswa. Etos kerja guru Pendidikan Agama Kristen dan pemahaman yang baik akan hakikat persiapan ujian semester sangat penting untuk diperhatikan. Kurangnya etos kerja dan kekurangpahaman guru Pendidikan Agama Kristen tentang persiapan ujian siswa akan mempengaruhi kesiapan siswa dalam menghadapi ujian semester. Demikian halnya dengan tahapan pelaksanaan persiapan ujian semester. Guru Pendidikan Agama Kristen perlu memahami setiap tahapan persiapan ujian tersebut. Etos kerja, pemahaman, dan pelaksanaan persiapan ujian semester yang baik merupakan strategi guru Pendidikan Agama Kristen dalam meningkatkan hasil belajar siswa.